2019
DOI: 10.1002/pssb.201900471
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Spectroscopic Characterization of Tb3+‐Doped MgAl2O4 Spinel Ceramics Fabricated by Spark Plasma Sintering Technique

Abstract: Spark plasma sintering (SPS) technique is successfully used for the preparation of magnesium aluminate spinel ceramics doped with different concentrations of Tb3+ ions. Structural, morphological, optical, and photoluminescence (PL) characterization are conducted. It is demonstrated that the redshift in the absorption spectra is possibly due to the energy gap between the valence and conduction bands reducing and the formation of a higher concentration of nonbridging oxygen with an increase in the concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…[21,22] How-ever, previous research reported the Er 3+ ions could replace not only the tetrahedral positions of Mg 2+ ions but also the octahedral positions of Al 3+ ions, due to the defect accumulation in the spinel structure. [23,24] Particularly, due to the cluster of Frenkel defect pairs in MAO spinel, the occupation of cations (Mg 2+ or Al 3+ ) at diverse sites is changed and the O interstitials recombine with the vacancies, which result in the structure transformation from ordered spinel to disordered spinel and further to disordered rock-salt. [25,26] Therefore, except the substitution of Mg 2+ and Al 3+ ions, Er 3+ ions enter into the vacancy sites, [27] resulting in the subsequent difference in EL performance.…”
Section: Resultsmentioning
confidence: 99%
“…[21,22] How-ever, previous research reported the Er 3+ ions could replace not only the tetrahedral positions of Mg 2+ ions but also the octahedral positions of Al 3+ ions, due to the defect accumulation in the spinel structure. [23,24] Particularly, due to the cluster of Frenkel defect pairs in MAO spinel, the occupation of cations (Mg 2+ or Al 3+ ) at diverse sites is changed and the O interstitials recombine with the vacancies, which result in the structure transformation from ordered spinel to disordered spinel and further to disordered rock-salt. [25,26] Therefore, except the substitution of Mg 2+ and Al 3+ ions, Er 3+ ions enter into the vacancy sites, [27] resulting in the subsequent difference in EL performance.…”
Section: Resultsmentioning
confidence: 99%
“…[ 15–24 ] Nevertheless, doping of such ceramics not only leads to modification of their luminescent properties and changes in phase composition, but also causes structural transformation. [ 25–27 ] Such significant transformation of the inner structure in ceramics facilitates the formation of additional defect‐related free volumes. [ 28–33 ]…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24] Nevertheless, doping of such ceramics not only leads to modification of their luminescent properties and changes in phase composition, but also causes structural transformation. [25][26][27] Such significant transformation of the inner structure in ceramics facilitates the formation of additional defect-related free volumes. [28][29][30][31][32][33] Among the less conventional but promising methods to study the defect-related free volumes in solids of different structural types is positron annihilation lifetime (PAL) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The MgAl 2 O 4 : 2% Tb 3+ phosphor presented the highest luminescence intensity, and the colour could be tuned by changing the Tb 3+ content (2 mol%). For the first time, Valiev et al [18,19] presented structural and spectroscopic investigations of MgAl 2 O 4 ceramics doped with different concentrations of Tb 3+ ions (0.1, 1 and 5 wt%) fabricated by spark plasma sintering (SPS). However, there are still the few reports on the luminescence regularity of MgAl 2 O 4 doped with higher concentrations of Tb 3+ ions.…”
Section: Introductionmentioning
confidence: 99%